Maternal near miss in low-resource areas - Goldenberg, Robert L. (2017)
OBJECTIVE:To describe the Global Network Near-Miss Maternal Mortality System and its application in seven sites.METHODS:In a population-based study, pregnant women eligible for enrollment in the Maternal and Newborn Health Registry at seven sites (Democratic Republic of the Congo; Guatemala; Belagavi and Nagpur, India; Kenya; Pakistan; and Zambia) between January 2014 and April 2016 were screened to identify those likely to have a near-miss event. The WHO maternal near-miss criteria were modified for low-resource settings. The ratio of near-miss events to maternal deaths was calculated.RESULTS:Among 122 707 women screened, 18 307 (15.0%) had a potential near-miss event, of whom 4866 (26.6%; 4.0% of all women) had a near-miss maternal event. The overall maternal mortality ratio was 155 per 100 000 live births. The ratio of near-miss events to maternal deaths was 26 to 1. The most common factors involved in near-miss cases were the hematologic/coagulation system, infection, and cardiovascular system.CONCLUSION:By using the Global Network Near-Miss Maternal Mortality System, large numbers of women were screened for near-miss events, including those delivering at home or a low-level maternity clinic. The 4.0% incidence of near-miss maternal mortality is similar to previously reported data. The ratio of 26 near-miss cases to 1 maternal death suggests that near miss might evaluate the impact of interventions more efficiently than maternal mortality.